Efforts to Reduce Academic Procrastination Behavior Through Group Counseling Services Behavioral Contract Technique Behavioral Approach of Class X Students of SMK Negeri 4 Medan - Panggabean, Khairunnisa; Deliati, Deliati; Harahap, Muhammad Fauzi (Lembaga Riset Mutiara Akbar, 2025)
Academic procrastination represents a significant issue that adversely affects students' academic performance within the school setting. This research seeks to address procrastination tendencies among grade X students at SMK Negeri 4 Medan by implementing group counseling sessions utilizing the behavior contract technique. Assessment findings revealed that a majority of the students in the class exhibited a high tendency to delay academic tasks, and lacked awareness of time management. Group counseling services were chosen as an approach because they were able to create dynamics of mutual support between members, and form a shared commitment to make behavioral changes. The behavior contract technique was applied to build student commitment through a written agreement containing agreed behavioral targets and rewards. It is estimated that through this approach, students can increase their responsibility, internal motivation, and discipline in completing academic tasks on time, thus having a positive impact on improving their learning achievement.